The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1104/pp.95.3.954
|View full text |Cite
|
Sign up to set email alerts
|

Acetaldehyde Stimulation of Net Gluconeogenic Carbon Movement from Applied Malic Acid in Tomato Fruit Pericarp Tissue

Abstract: Applied acetaldehyde is known to lead to sugar accumulation in fruit including tomatoes (Lycopersicon esculentum) (O Paz, HW Janes, BA Prevost, C Frenkel [1982] presumably due to stimulation of gluconeogenesis. This conjecture was examined using tomato fruit pencarp discs as a test system and applied -[U-14C]malic acid as the source for gluconeogenic carbon mobilization. The label from malate was recovered in respiratory C02, in other organic acids, in ethanol insoluble material, and an appreciable amount i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 19 publications
(36 reference statements)
1
22
2
Order By: Relevance
“…These results indicate that the modified PEPCK level directly affects the sugar and organic acid contents, likely through gluconeogenesis. While it has been reported that the predominant metabolic flow in the flesh of tomato and grape is glycolysis (Carrari et al 2006;Famiani et al 2014), early labelling studies demonstrated that gluconeogenesis occurs during tomato fruit ripening (Farineau and Laval-Martin 1977;Halinska and Frenkel 1991). Our present results indicate that gluconeogenesis is involved in sugar accumulation in fruit, and PEPCK plays a regulatory role in this process.…”
Section: Discussionsupporting
confidence: 59%
“…These results indicate that the modified PEPCK level directly affects the sugar and organic acid contents, likely through gluconeogenesis. While it has been reported that the predominant metabolic flow in the flesh of tomato and grape is glycolysis (Carrari et al 2006;Famiani et al 2014), early labelling studies demonstrated that gluconeogenesis occurs during tomato fruit ripening (Farineau and Laval-Martin 1977;Halinska and Frenkel 1991). Our present results indicate that gluconeogenesis is involved in sugar accumulation in fruit, and PEPCK plays a regulatory role in this process.…”
Section: Discussionsupporting
confidence: 59%
“…Bahrami et al (2001) isolated the gene from tomato and showed that its expression increases during ripening. Although previous labeling studies have demonstrated that gluconeogenesis occurs in ripening tomato fruit (Farineau and Laval-Martin, 1977;Halinska and Frenkel, 1991), and cold-inducible PEPCK was reported in rapeseed (Sáez-Vásquez et al, 1995), its regulation in response to abiotic stress is not fully understood in plants. Our data suggest that salinity stress enhances gluconeogenesis, as well as metabolic flow in ripe fruit, resulting in high-Brix fruit.…”
Section: Resultsmentioning
confidence: 99%
“…In fruit development under such conditions, substantial restrictions in translocation from leaf to fruit, in carbon metabolism, and induction of gluconeogenesis from organic acid may occur; then, PEPC and PEPCK activities of fruit may play a key role for sugar accumulation and acid reduction. In grape, cherry, and tomato, there is evidence that gluconeogenesis from malate may occur (Halinska and Frenkel, 1991;Leegood and Walker, 1999).…”
Section: Discussionmentioning
confidence: 99%